Mutu Hedonik, Kandungan Kalsium dan Protein pada Mi Kering dengan Substitusi Tepung Tulang Ikan Patin (Pangasius Sp.): Hedonic Quality, Calcium and Protein Content in Dry Noodles with Substitution of Patin Fish (Pangasius Sp.) Bone Flour - Wahyu Rachmawati; Dyah Kartika Wening (JURNAL GIZI DAN KESEHATAN, 2023)
Pangasius fish bone is a byproduct of fish processing that contains macro and micro minerals, including calcium and essential proteins for bodily health. Therefore, a dried noodle product with substituted pangasius fish bone flour was developed and subjected to hedonic quality testing to determine consumer preferences towards the resulting product. To assess hedonic quality, calcium, and protein content of dried noodles with substituted pangasius fish bone flour. This study employed an Experimental Design approach. Treatments involved creating dried noodles with 5%, 10%, and 15% substitution of pangasius fish bone flour, followed by hedonic quality testing to determine the optimal formula. Subsequently, calcium and protein content analysis was conducted. Hedonic quality testing results for each formula of dried noodles with pangasius fish bone flour substitution yielded the following scores: F1 - color 4.32, aroma 3.24, taste 3.40, texture 3.68; F2 - color 4.00, aroma 3.20, taste 3.04, texture 3.32; F3 - color 3.96, aroma 2.36, taste 3.00, texture 3.12. The nutritional content of dried noodles with pangasius fish bone flour substitution in formula 1 exhibited an average calcium content of 239.25 mg/50g and protein content of 3.7%. The selected formula is formula 1, which contains 239.25 mg of calcium and 7.4% (equivalent to 3.7 grams) of protein in each serving of 50 grams. ABSTRAK Tulang ikan patin merupakan limbah pengolahan ikan yang mengandung mineral makro dan mikro di antaranya kalsium dan protein yang penting bagi kesehatan tubuh. Oleh karena itu, produk mi kering dengan substitusi tepung tulang ikan patin dikembangkan dan diuji mutu hedoniknya untuk mengetahui preferensi konsumen terhadap produk yang dihasilkan. Untuk mengetahui mutu hedonik, kandungan kalsium dan protein mi kering substitusi tepung tulang ikan patin. Penelitian ini merupakan penelitian Experimental Design. Perlakuan dilakukan dengan membuat mi kering dengan substitusi tepung tulang ikan patin sebesar 5%, 10%, dan 15% kemudian dilakukan uji mutu hedonik untuk mengetahui formula terbaik yang akan dilanjutkan dengan analisis kandungan kalsium dan protein.  Hasil uji mutu hedonik setiap formula mi kering substitusi tepung tulang ikan patin pada F1 untuk parameter warna sebesar 4,32. aroma 3,24, rasa 3,40, tekstur 3,68, F2 untuk parameter warna sebesar 4, aroma 3,20, rasa 3,04, tekstur 3,32, F3 untuk parameter warna sebesar 3,96, aroma 2,36, rasa 3, tekstur 3,12. Kandungan zat gizi mi kering substitusi tepung tulang ikan patin pada formula 1 dengan rata-rata kalsium 239,25 mg/50g dan protein 3,7% atau 3,7 g/50g. Formula terpilih adalah formula 1 dengan kandungan kalsium sebesar 239,25 mg dan kandungan protein sebesar 7,4% atau 3,7 gram dalam setiap sajiannya yang berisi 50 gram.